Introducing Bayer Liquor-Derived Geopolymers - Kealley, Cat; Jamieson, E.; van Riessen, Arie; McLellan, B.; Penna, B.; Nikraz, Hamid (2016)
In this handbook, the editors and contributors have paid extra attention to the emissions generated by coarse aggregates, emissions due to fine aggregates, and emissions due to cement, fly ash, GGBFS, and admixtures.